2019
DOI: 10.1016/j.bja.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Using the 6-minute walk test to predict disability-free survival after major surgery

Abstract: Background: The 6-min walk test (6MWT) is a common means of functional assessment. Its relationship to disability-free survival (DFS) is uncertain. Methods: This sub-study of the Measurement of Exercise Tolerance for Surgery study had co-primary outcome measures: correlation of the preoperative 6MWT distance with 30 day quality of recovery (15-item quality of recovery) and 12 month WHO Disability Assessment Schedule scores. The prognostic utility of the 6MWT and other risk assessment tools for 12 month DFS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 25 publications
1
37
1
4
Order By: Relevance
“…25,26 As part of a pre-specified substudy on the prognostic performance of the 6 min walk test, the WHODAS questionnaire was administered before surgery and subsequently at 1 yr post-surgery. 27 The questionnaire consists of 12 items, each of which is scored 0e4. The sum of all item responses is the WHODAS disability score, which ranges from 0 to 40 and can be expressed as a Table 1 Characteristics of the study sample.…”
Section: Subset Analysis On New Postoperative Disabilitymentioning
confidence: 99%
“…25,26 As part of a pre-specified substudy on the prognostic performance of the 6 min walk test, the WHODAS questionnaire was administered before surgery and subsequently at 1 yr post-surgery. 27 The questionnaire consists of 12 items, each of which is scored 0e4. The sum of all item responses is the WHODAS disability score, which ranges from 0 to 40 and can be expressed as a Table 1 Characteristics of the study sample.…”
Section: Subset Analysis On New Postoperative Disabilitymentioning
confidence: 99%
“…Several studies have determined the relation between the 6MWT and postoperative (cardiac) complications and mortality. 23,[26][27][28] Those studies showed conflicting results but overall no good relation between the 6MWT and postoperative complications. 25 However, some more recent studies showed a good relation between a low 6MWT and cardiopulmonary complications.…”
Section: The Literaturementioning
confidence: 99%
“…26,27 Finally, a recent study by Shulman and colleagues in patients undergoing major surgery showed that the 6MWT was predictive of death and myocardial infarction. 28 Gait speed is another test for functional capacity and is used in elderly patients in the assessment of frailty. 29 There is a relation between low gait speed and increased mortality in elderly patients undergoing cardiac surgery.…”
Section: The Literaturementioning
confidence: 99%
“…Six-minute walk test distance is strongly correlated with the ventilatory threshold and distance can be used to risk stratify patients before major noncardiac surgery. 35,36 Additionally, Reddy et al identified the time to complete an inclinic stair climb test as the single strongest predictor of perioperative complications in patients undergoing major abdominal surgery, and this test outperformed the American College of Surgeons National Surgical Quality Program score (area under the curve, 0.81 vs. 0.62; P < 0.0001). 37 More objective measures of patient physical activity, either through patient worn accelerometers or brief exercise tests, may further improve perioperative risk stratification.…”
Section: Discussionmentioning
confidence: 99%